Mechanism of Action of Berberine in Attenuating LPS-induced Acute Lung Injury in Mouse Cells - Guo, Anqing; Ding, Hui (Journal of Contemporary Medical Practice, 2025)
Objective: To explore the mechanism of berberine in alleviating acute lung injury and related pathway targets. Methods: Lipopolysaccharide was used to construct a model of acute lung injury, and the specific binding proteins were screened by berberine molecular probes, and the binding proteins were analyzed by bioinformatics. Results: Berberine and its probes significantly reduced the content of inflammatory factors (TNF-α), and GO analysis showed that the biochemical process of target protein enrichment was the response to estrogen stimulation and the connection of unfolded proteins in molecular function. Involved in protein processing in the endoplasmic reticulum in the KEGG analysis pathway. Conclusion: Berberine can alleviate acute lung injury by stimulating estrogen to participate in protein processing in the endoplasmic reticulum.